Kajian Perubahan Sosial Ekonomi Masyarakat Di Sekitar Pelabuhan Amurang Kecamatan Amurang Barat Kabupaten minahasa Selatan - Kalele, Selvy R (JURNAL ILMIAH SOCIETY, 2015)
Development is basically a process of continuous and planned activities which is meant to change and improve the quality of socio – economic life towards a better and natural condition from time to time.If the development is incompatible with the socio – economic aspect in a certain region, it can then be said to be unsuccessfull.The aims of this research are to the describe and to analyze the socio-economic changes of the community around the harbour of Amurang, South Minahasa Regency.The method of research applies qualitative approach by collecting the data using in-depth interviews from twenty informants selected on the basis of certain considerations called sampling with purpose